Structural analysis of mangrove tree vegetation in the channel Furo Grande in Bragança, Pará - Seixa, Joaquim Augusto Souza de; Fernandes, Marcus Emanuel Barroncas; Silva, Ederly Santos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The present study aims to describe the structural attributes of the mangrove stands at the Furo Grande, Bragança, Pará, emphasizing the patterns of spatial distribution of the vegetation in 25 quadrats of 20x20 m. For every tree inside the plots the following measures were taken: Diameter at Breast Height (DBH), Height and Crown Width. Measurements were taken from 1211 individuals of two species, Rhizophora mangle and Avicennia germinans, distributed between three sites. At Site nº1, dominated by A. germinans, 255 trees of A. germinans (93.07%) were measured and 19 of R. mangle (6.93%), totalling 274 individuals. Site nº2, dominated by R. mangle, presented 382 trees of R. mangle (90.31%) and 41 of A. germinans (9.69%), totalling 423 individuals. Site nº3 presented 269 trees of A. germinans (52.33%) and 245 of R. mangle (47.67%), totalling 514 individuals. The most abundant species in the present study was R. mangle with 646 individuals. The analysis of the structural parameters presented significant differences between DBH x Density (F=6.07; gl=24; p<0.05), DBH x Height (F=18.70; gl=24; p<0.001) and Crown Width x DBH (F=47.15; gl=23; p<0.001). Of the three sites, density values showed Site nº1 (dominated by A. germinans) as the most developed. This difference is corroborated by high mean values of Height and DBH. The results on structural attributes and floristic composition of mangrove stands at the Furo Grande seem to indicate that these biotic factors can be influenced by other biotic factors, such as competition and natural succession of senescent individuals.